2022
DOI: 10.3390/ijerph19095444
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Helminthic Co-Infection during Pregnancy in Sub-Saharan Africa: A Systematic Review and Meta-Analysis

Abstract: Malaria and helminthic co-infection during pregnancy causes fetomaternal haemorrhage and foetal growth retardation. This study determined the pooled burden of pregnancy malaria and helminthic co-infection in sub-Saharan Africa. CINAHL, EMBASE, Google Scholar, Scopus, PubMed, and Web of Science databases were used to retrieve data from the literature, without restricting language and publication year. The Joanna Briggs Institute’s critical appraisal tool for prevalence studies was used for quality assessment. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 186 publications
0
4
0
Order By: Relevance
“…Fetal deaths in Ghana, in contrast, were found to be associated with fetal infections in 9.7% to 13.0% of cases [ 3 , 4 ] and placental inflammation in up to 24.8% of cases [ 4 ]. As repeatedly demonstrated, viral, bacterial, mycobacterial and parasitological infections threaten the health of mother and fetus [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For Ivory Coast, fewer respective studies have been published, but available data nevertheless indicate relevant pregnancy-associated infection risks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal deaths in Ghana, in contrast, were found to be associated with fetal infections in 9.7% to 13.0% of cases [ 3 , 4 ] and placental inflammation in up to 24.8% of cases [ 4 ]. As repeatedly demonstrated, viral, bacterial, mycobacterial and parasitological infections threaten the health of mother and fetus [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For Ivory Coast, fewer respective studies have been published, but available data nevertheless indicate relevant pregnancy-associated infection risks [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mangusho et al have shown that 26.1% of pregnant women in Uganda had P. falciparum malaria [11]. Recently, in their meta-analysis of 24 studies (n = 14,087 pregnant women), Boltena et al [19] indicated that the pooled prevalence of malaria in sub-Saharan Africa was 33.0%. Moreover, a previous meta-analysis of 35 studies indicated that the overall prevalence of asymptomatic P. falciparum infection was 26.1% in pregnant women in sub-Saharan Africa [9].…”
Section: Discussionmentioning
confidence: 99%
“…About 1.5 billion infections resulting from malaria and helminthiases contribute to pregnancy-related morbidity and mortality [ 1 ], exposing the foetus to several complications including anaemia, still birth, intrauterine growth retardation, and low birth weight infants [ 2 , 3 ]. Malaria and schistosomiasis are widespread parasitic infections in tropical and subtropical regions including Ghana [ 4 , 5 ] and pose a double disease burden during pregnancy in coendemic areas.…”
Section: Introductionmentioning
confidence: 99%